2022
DOI: 10.2106/jbjs.21.01415
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Nonoperative Procedures for Knee Osteoarthritis in the Year Prior to Primary Total Knee Arthroplasty

Abstract: Background:The convergence of national priorities to reduce health-care costs and deliver high-value care warrants the need to examine health-care utilization. The objective of this study was to describe the costs associated with nonoperative procedures in the 1-year period leading up to primary total knee arthroplasty (TKA).Methods:An observational cohort study was conducted using the IBM Watson Health MarketScan databases. Patients with late-stage knee osteoarthritis (OA) who underwent unilateral, isolated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…A case-cohort study by Bruin et al [ 16 ] found that perioperative dosing of PPIs is associated with increased prosthetic joint infections. According to a multicenter, cross-sectional study conducted in 2022 in Japan, the mean age of new patients with hip osteoarthritis was 63.5 years [ 53 ], and those patients with osteoarthritis may undergo joint replacement surgery after taking NSAIDs for an extended duration [ 54 ]. However, infection and periprosthetic fractures are serious complications of joint replacement surgery [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A case-cohort study by Bruin et al [ 16 ] found that perioperative dosing of PPIs is associated with increased prosthetic joint infections. According to a multicenter, cross-sectional study conducted in 2022 in Japan, the mean age of new patients with hip osteoarthritis was 63.5 years [ 53 ], and those patients with osteoarthritis may undergo joint replacement surgery after taking NSAIDs for an extended duration [ 54 ]. However, infection and periprosthetic fractures are serious complications of joint replacement surgery [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-operative procedure for knee OA is physical therapy, bracing, intra-articular injections (hyaluronic and corticosteroids), and medications (opioids, NSAIDS, and acetaminophen), and knee-specific imaging (see table 2 for specific codes used to identify these procedures). 38 Medications will be identified from the outpatient pharmaceutical database, with non-steroidal anti-inflammatory drugs (NSAIDS) and opioids being identified through NDCs and acetaminophen identified based on the generic name in RED BOOK. 39 40…”
Section: Methods and Analysismentioning
confidence: 99%
“…This excellent paper from Boston (Massachusetts, USA) set out to identify what the costs of these nonoperative interventions were using the MarketScan methodology. 6 They included all nonoperative intervention types on which there were available data (physical therapy, bracing, and intra-articular injections (hyaluronic acid, and corticosteroids)), along with prescriptions of medications and obtaining knee-specific imaging. In this study of 24,492 total knee arthroplasty patients, the costs of nonoperative procedures were $1,355 (standard deviation 2,087), despite the late stage of the disease in this group.…”
Section: What Is the Cost Of Nonoperative Interventions For Knee Oste...mentioning
confidence: 99%